Network Security Threats and Countermeasures on Cloud Computing - Ping Yao; Hong Li (Dianxin kexue)
Cloud computing is a new concept of providing virtualized resources to the consumers.Consumers can request a cloud for services,applications,solution and can store large amount of data in different locations.But with the growing popularity of cloud computing,the increasing risk of security is becoming a main and top issue.The type of cloud computing and the network security issues were discussed.A backup plan required for overcoming the network security issues in cloud computing was proposed.